Association between vasectomy and risk of testicular cancer: A systematic review and meta-analysis. - Haifeng Duan; Tuo Deng; Yiwen Chen; Zhijian Zhao; Yaoan Wen; Yeda Chen; Xiaohang Li; Guohua Zeng (PLoS ONE)
Objectives A number of researchers have reported that vasectomy is a risk factor for testicular cancer. However, this conclusion is inconsistent with a number of other published articles. Hence, we conducted this meta-analysis to assess whether vasectomy increases the risk of testicular cancer. Materials and methods We identified all related studies by searching the PubMed, Embase, and Cochrane Library database from January 01, 1980 to June 01, 2017. The Newcastle-Ottawa Scale (NOS) checklist was used to assess all included non-randomized studies. Summarized odds ratios (ORs) and 95% confidence intervals (CIs) were used to assess the difference in outcomes between case and control groups. Subgroup analyses were performed according to the study design and country. Results A total of eight studies (2176 testicular cancer patients) were included in this systematic review and meta-analysis. Six articles were case-control studies, and two were cohort studies. The pooled estimate of the OR was 1.10 (95% CI: 0.93-1.30) based on the eight studies in a fixed effects model. Two subgroup analyses were performed according to the study design and country. The results were consistent with the overall findings. Publication bias was detected by Begg's test and Egger's test and p values > 0.05, respectively. Conclusions Our meta-analysis suggested that there was no association between vasectomy and the development of testicular cancer. More high-quality studies are warranted to further explore the association between vasectomy and risk of testicular cancer.